Spectacle and display : a modern history of Britain's Roman mosaic pavements - Dawson, M. 1955- (Archaeopress Roman archaeology ;, 2021)
Antiquarian interest in the Roman period mosaics of Britain began in the 16th century. This book explores responses and attitudes to mosaics, not just at the point of discovery but during their subsequent history. It is a field which has received scant attention and provides a compelling insight into the agency of these remains.